Implementasi Peran Guru guna Memotivasi Siswa pada Pembelajaran SKI di Kelas IV MI Nurul Huda Kota Bengkulu - Ismail, Aulia; Melyasari, Eliza; Cahyani, Widya; Alimni, Alimni (Asian Journal of Early Childhood and Elementary Education, 2024)
The role of teacher in enhancing students' learning motivation is an integral activity in the learning process. Besides transferring and channeling their knowledge, a teacher plays a role in arousing students' enthusiasm. Its implications are seen in the success of students in achieving learning targets where, in the learning process, teachers must have well-planned strategies to achieve optimal results. The focus of this research is to identify the role of teachers in encouraging students' learning motivation, especially in HIC (History of Islamic Culture) subject. This study uses a qualitative method with a descriptive approach by conducting observations and interviews with HIC (History of Islamic Culture) subject teachers at MI Nurul Huda Kota Bengkulu Class IV. The findings indicate that in History of Islamic Culture, teachers have not been able to create effective learning, as seen from the learning process where students are not very enthusiastic and lack excitement during History of Islamic Culture Subject. The learning process is successful when students have enthusiasm for learning. Therefore, it is important for teachers to be able to enhance students' learning motivation. Teachers are required to be creative in stimulating students' learning motivation.